Network Management Method Based on Optimal Control - Zhi Chai (Dianxin kexue)
With the development of access network technology,the burden of network management has greatly increased,and became more frequent.In such case,the network management will not only make the network system in good condition,but also need to make sure that the adjustment process of network is optimized.From the viewpoint of cybernetics,the problem in network management was studied.Based on optimal control theory,a method to optimize network management was proposed.The research results have been verified in Tianjin Unicom's network management system,the research on automatic control theory in network management will take important influence in this field.